Värmeflöden genom gröna tak i subarktiskt klimat : En studie av det gröna taket på Sjunde Huset i Kiruna - Nilsson, Linda (Luleå tekniska universitet, Arkitektur och vatten, 2018)
Some of the problems with today’s urban civilizations are the lack of green areas and that the cities are getting warmer and warmer. Building green roofs contributes to a reduced greenhouse effect, as plants have a cooling effect that reduces the heat generated in both houses and cities. The greenhouse effect is reduced by the fact that the plants on the roof reflect much more solar energy than a black ceiling, which instead absorbs the heat. The plants help to make the building more energy efficient. Green roofs also contribute to the emergence of new green areas in cities where the settlement has taken over the city. The purpose of the study has been to, from an energy perspective, examine the advantages and potential disadvantages of green roof energy performance in the subarctic climate. The study has been conducted by analyzing measured heat flow and temperature conditions during a winter season. The study was delimited to the green roof of Sjunde Huset in Kiruna, Norrbotten, Sweden. The research questions examined are the advantages and disadvantages of energy performance for green roofs, how does the energy performance vary for green roofs in cold climate during the season and what energy performance has the green roof under investigation in the subarctic climate. The study has been done through analysis of measurement data to see if the cooling effect from an energy perspective can be a disadvantage in a so-called subarctic climate. The analysis has also investigated whether the heat-insulating and heat-storing effect can be an advantage from an energy perspective in a so-called subarctic climate. The test period under review is from October 25, 2016 to January 4, 2017. The test period shows changes at different times. These times have been explored more closely. Collected measurement data has been analyzed using Excel chart against data for different weather conditions from SMHI. The different weather conditions are solar time, global radiation, wind speed and wind direction. Parameters that are also ...